NPF signaling-dependent maintenance of metabolic homeostasis in the pea aphid is mediated by a highly selective ligand-receptor interaction and tissue-specific changes in NPF and NPFR - Cissy Huygens; Mélanie Ribeiro Lopes; El-Sayed Baz; Jozef Vanden Broeck; Federica Calevro; Patrick Callaerts (Heliyon)
Neuropeptide F (NPF) and its receptor (NPFR) are important regulators of food intake, physiology and metabolism in insects. Focusing on a major crop pest, the pea aphid Acyrthosiphon pisum, it is shown that the predicted NPFR is a highly selective NPF receptor. Its activation by NPFs from other insect species shows high specificity and reflects evolutionary distance. Expression analyses showed high expression of npf and npfr mRNAs in young nymphs. In young adults, npf is selectively expressed in the head and NPF peptide localizes to six neurons, of which four in the pars intercerebralis, a major neuroendocrine center in insects. Strong expression of npfr is observed in head and gut. Finally, starvation leads to tissue-specific changes in expression of npf and npfr and provides evidence for NPF signaling in fat body and bacteriocytes and a hunger response by the developing embryos. NPF injection increases lipid content. These results identify the brain-gut axis as central to NPF signaling in aphids in promoting growth and maintaining metabolic homeostasis while the selective activation of the receptor reveals the potential for developing selective biopesticides targeting this receptor.